Condom-use Skills Checklist: A Proxy for Assessing Condom-use Knowledge and Skills When Direct Observation Is Not Possible - Stanton, B; Deveaux, L; Lunn, S; Yu, S; Brathwaite, N; Li, X; Cottrell, L; Harris, C; Clemens, R; Marshall, S (Journal of Health, Population and Nutrition, 2009)
Because of the continued importance of correct condom-use in controlling the HIV epidemic and the limited availability of tools for assessing correct condom-use, methods for assessing condom-application skills, especially when direct observation is not feasible, are needed. Accordingly, in the context of a high-risk population (The Bahamas) for HIV, a 17-item scale-the Condom-use Skills Checklist (CUSC)-was developed for use among young adolescents and adults. The rationale and approach to developing the scale and some measures of internal consistency, construct validity, and criterion-related validity have been described. It is concluded that the scale offers a reasonable alternative to direct observation among older subjects and that further development may make it more useful among pre-adolescents. Key words: Condom-use; Interventions; Knowledge; Scale; Skills; Bahamas doi: 10.3329/jhpn.v27i3.3383 J Health Popul Nutr 2009 Jun;27(3):406-413